Retrofitting masonry and cavity brick façades for different noise zones using laboratory measurements. Issue 2 (June 2017) - Demirkale, Sevtap Yilmaz; Ascigil-Dincer, Mine
Façade airborne sound insulation is crucial for protection of indoor environment from environmental noise. In Turkey, sound insulation in new buildings is bound by law, but 6 million pre-1980 dwellings with thin brick walls and single-glazed windows used in highly transparent façades should be retrofitted. In this study, sound reduction index of masonry and cavity exterior walls which consist of brick, mortar, gypsum board and mineral wool and of common window types is measured in sound insulation test rooms. The study compares and evaluates the effects of plaster, brick thickness, cavity depth, mineral wool thickness and mineral wool placement on sound reduction index values, using traditional materials and building techniques. Traditional brick wall façades and possible retrofitting of these façades are evaluated for sound insulation of bedrooms and living rooms in different noise zones, 55, 60, 65, 70 and 75 dBA, with various transparency ratios, 0%, 30%, 40%, 50% and 70%. The analysis shows that window types and single-layer walls are the deterministic factors in evaluating sound insulation in retrofitting projects and that it is not possible to provide proper aural comfort in high noise zones.